2005
DOI: 10.1073/pnas.0409227102
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical studies identify tobacco SABP2 as a methyl salicylate esterase and implicate it in plant innate immunity

Abstract: Salicylic acid (SA) is a critical signal for the activation of plant defense responses against pathogen infections. We recently identified SA-binding protein 2 (SABP2) from tobacco as a protein that displays high affinity for SA and plays a crucial role in the activation of systemic acquired resistance to plant pathogens. Here we report the crystal structures of SABP2, alone and in complex with SA at up to 2.1-Å resolution. The structures confirm that SABP2 is a member of the ␣͞␤ hydrolase superfamily of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
252
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(268 citation statements)
references
References 44 publications
(57 reference statements)
7
252
1
3
Order By: Relevance
“…These authors demonstrated that MeSA could be transmitted to neighboring plants and subsequently induce their defensive mechanisms by converting MeSA into salicylic acid. The enzyme SABP2 (for salicylic acid-binding protein) mediating the conversion of MeSA into salicylic acid has been identified (Forouhar et al, 2005). Thus, MeSA acts as mobile signal molecule in systemic acquired resistance (Park et al, 2007).…”
Section: Emission Of Php Volatiles From Tomato Fruit Upon Tissue Disrmentioning
confidence: 99%
“…These authors demonstrated that MeSA could be transmitted to neighboring plants and subsequently induce their defensive mechanisms by converting MeSA into salicylic acid. The enzyme SABP2 (for salicylic acid-binding protein) mediating the conversion of MeSA into salicylic acid has been identified (Forouhar et al, 2005). Thus, MeSA acts as mobile signal molecule in systemic acquired resistance (Park et al, 2007).…”
Section: Emission Of Php Volatiles From Tomato Fruit Upon Tissue Disrmentioning
confidence: 99%
“…A model has been proposed in which the SA accumulating after tobacco mosaic virus (TMV) infection is converted to MeSA by SA methyl transferase (SAMT1) in inoculated tobacco leaves, and MeSA subsequently travels through the phloem to distant leaves. Here, by the methyl esterase activity of SA binding protein2 (Forouhar et al, 2005), MeSA is reconverted to active SA, which in turn triggers SAR in systemic tissue (Park et al, 2007). In addition to its movement through the phloem, MeSA has been suggested to act as a volatile intraplant signal that is capable of activating SAR in distant leaves of the same plant (Shulaev et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of SA is often correlated with an increase in ROS production during plant stress response (for review, see Herrera-Vásquez et al, 2015). A series of SA binding proteins has been identified, notably catalase (Chen et al, 1993a), peroxidase (Durner and Klessig, 1995), and methyl-salicylate esterase (Forouhar et al, 2005) that appear to explain this correlation, but their roles as general SA receptors have been controversial (Attaran et al, 2009;Bi et al, 1995). Further sets of SA binding proteins in Arabidopsis have been identified by affinity screens and include several mitochondrial enzymes and also GSTs including GSTF8, which showed enzymatic inhibition by SA (Manohar et al, 2015;Tian et al, 2012).…”
mentioning
confidence: 99%